CodeTalk: Improving Programming Environment Accessibility for Visually Impaired Developers - Potluri, Venkatesh; Vaithilingam, Priyan; Iyengar, Suresh; Vidhya, Y.; Manohar, Swami; Srinivasa, Gopal (CHI 2018, 2018)
In recent times, programming environments like Visual Studio are widely used to enhance programmer productivity. However, inadequate accessibility prevents Visually Impaired (VI) developers from taking full advantage of these environments. In this paper, we focus on the accessibility challenges faced by the VI developers in using Graphical User Interface (GUI) based programming environments. Based on a survey of VI developers and based on two of the authors’ personal experiences, we categorize the accessibility difficulties into Discoverability, Glanceability, Navigability, and Alertability. We propose solutions to some of these challenges and implement these in CodeTalk, a plugin for Visual Studio. We show how CodeTalk improves developer experience and share promising early feedback from VI developers who used our plugin.
Honorable Mention